Component rights between constitutional approval and judicial protection - Ahmed, Shakhwan Saber (Journal of Legal and Political Studies, 2023)
Constitutional recognition of the rights of the components in a country with multiple ethnic, religious, and sectarian terms is not sufficient to guarantee the rights of all components in it, if there is no constitutional jurisdiction that is a watchdog on the legislative authority that translates the constitutional texts into ordinary legislation in the light of those texts, so that these components can enjoy the practice Their rights and freedoms established for them in the constitution, and that the Iraqi constitution of 2005 approved a number of political, administrative, religious and linguistic rights for the Iraqi components, as well as the constitution establishing the establishment of a Federal Supreme Court with one of its specializations overseeing the constitutionality of laws. In the context of exercising this jurisdiction, the court was able to protect the rights established in the constitution for all components of the Iraqi people.
Keywords: Constitutional recognition; rights; ordinary legislation; constitutional jurisdiction; legislative authorit